Strangeville School is totally normal - Miller, Darcy, 1981- (Strangeville School, 2021)
"Harvey Hill's first day at Strangeville Middle School doesn't go quite as expected when he discovers it's full of various creatures and odd happenings, including a particularly nefarious supply closet"--